The Efficacy of Treatment of Different Intervention Programs for Patellofemoral Pain Syndrome–A Single Blinded Randomized Clinical Trial. Pilot Study - Feazadeh Avraham; Saposhnik Aviv; Pnina Ya'akobi; Hava Faran; Zilla Fisher; Yael Goldman; Guy Neeman; Eli Carmeli (The Scientific World Journal)
Patello-femoral pain syndrome (PFPS) is a common knee joint disability. The integration of hip soft tissue regimens are not always emphasized, although current literature implies that there is a significant relationship between the two and there is a lack of randomized clinical trials to substantiate this relationship in clinical practice. A randomized controlled assessor blinded trial was designed to explore different rehabilitation programs related to PFPS. The study was conducted at RAZIEL institute of physical therapy, Netania, Israel with a total of 30 consecutive patients (mean age 35y), diagnosed with PFPS. All patients were randomly allocated into 3 groups. Group I conventional knee rehabilitation program. Included quadriceps strengthening and Trans Electric Neuromuscular Stimulation (TENS). Group II hip oriented rehabilitation program. included stretching, Hip external rotators strengthening and TENS. Group III a combination of the two above programs. Pain and function were documented on initial of the program and again 3 weeks later, on the completion. Pain was assessed by a numeric visual analogue scale (VAS); function was assessed by Patello-femoral joint evaluation scale (PFJES) (0-100 points). At end of trial, all groups showed significant improvements in VAS and PFJES (p<0.0001); these improvements did not vary significantly between the 3 groups. The conclusions were that the explored different rehabilitation programs showed a similar beneficial effect.